2020
DOI: 10.1136/sextrans-2019-054249
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity rate and sociodemographic factors associated to HIV, HBV, HCV and syphilis among parturients from Irene Neto Maternity of Lubango city, Angola

Abstract: ObjectivesTo characterise infections by HIV, Treponema pallidum, hepatitis B (HBV) and C virus (HCV) in parturients admitted to Irene Neto Maternity, Lubango city, Huíla province, Angola, namely its seropositivity rate and its association with sociodemographic factors.MethodsAn observational, cross-sectional and analytical facility-based survey was conducted among 500 parturients at Irene Neto Maternity, from October 2016 to September 2017. Women in labour were screened for antibodies against HIV-1/2, T. palli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…We found that the decreasing HIV prevalence among pregnant women was consistent with other studies based in China [13,14,18]. The HIV prevalence reported in this study was lower than that reported in other countries, such as Cameroon (5.70% in 2017) [28], Ethiopia (4.1% in 2011-2014) [29] and Angola (3.0% in 2017) [30]. Simultaneously, the prevalence of syphilis and HCV was also comparatively lower than reported in other studies [28][29][30][31][32], which was higher than 1% for both.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the decreasing HIV prevalence among pregnant women was consistent with other studies based in China [13,14,18]. The HIV prevalence reported in this study was lower than that reported in other countries, such as Cameroon (5.70% in 2017) [28], Ethiopia (4.1% in 2011-2014) [29] and Angola (3.0% in 2017) [30]. Simultaneously, the prevalence of syphilis and HCV was also comparatively lower than reported in other studies [28][29][30][31][32], which was higher than 1% for both.…”
Section: Discussionsupporting
confidence: 91%
“…The HIV prevalence reported in this study was lower than that reported in other countries, such as Cameroon (5.70% in 2017) [28], Ethiopia (4.1% in 2011-2014) [29] and Angola (3.0% in 2017) [30]. Simultaneously, the prevalence of syphilis and HCV was also comparatively lower than reported in other studies [28][29][30][31][32], which was higher than 1% for both. Several reasons could explain the decreasing trend of STI prevalence among pregnant women in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…An observational, cross-sectional, analytical facility-based survey was conducted among 500 parturients at INM, from October 2016 to September 2017 [5]. INM is the reference maternity in Huíla, the second most populous province in Angola.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were obtained from 57 newborns of 36, 12, four and two mothers infected with HBV, HIV-1, T. pallidum and HBV/HIV-1, respectively [5]. There were three twin pregnancies among the former, totalizing 41 newborns from HBV-infected mothers.…”
Section: Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation